Digital Exposure and Adolescent Mental Health: A Decade Review of Social Comparison Impact - Ashakumari P; Vijayakumar K. S (Journal of Psychology and Social Sciences, 2026)
Over the last decade, digital platforms have become an integral part of adolescents’ lives. This paper aims to examine the impact of constant exposure to digital social environments on adolescent mental health from 2015 to 2025. It emphasizes the role of digital platforms in influencing thoughts, feelings, overall personality development, and mental health outcomes among young people. This review highlights key psychological mechanisms, notably upward social comparison, through which adolescents evaluate themselves against idealized depictions of appearance, abilities, and success. Growing evidence links these processes to body dissatisfaction, lowered self-esteem, anxiety, and depressive symptoms. Furthermore, this paper addresses moderating factors such as gender differences and active versus passive usage patterns, alongside post-pandemic challenges arising from heightened screen engagement during COVID-19. Finally, the necessity of psychoeducational interventions, digital literacy, and multi-tiered social support systems to foster resilience is discussed.